2012
DOI: 10.1111/j.1540-4781.2012.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Lexicalized Aspectual Usage in Oral Proficiency Interviews

Abstract: This study suggests that Intermediate High and Advanced speakers produce aspectually valid constructions in Oral Proficiency Interviews (OPIs) in large part because they are doing more than assigning aspect to lexical categories (Lexical aspect hypothesis), but because they are assigning lexicalized meaning to discrete verbs, for example govorit' (imperfective)-'to talk,' but skazat' (perfective)-'to say.' Analysis of the data from 55 OPIs conducted with second language (L2) Russian speakers ranging from Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This is not to say that L2 Russian speakers rated Advanced (Low, Mid, or High) do not demonstrate control of aspect in OPIs. Advanced speakers' aspectual accuracy has been found to be high—89% to 92% percent accurate across the Advanced range, as one would expect by reading the ACTFL Guidelines (Robin, in press). But Robin found that that apparent accuracy owes itself to the high degree of lexicalization of frequently occurring verbs (40.5% in Advanced Low and Mid; 37.5% in Advanced High).…”
Section: Discussionmentioning
confidence: 82%
“…This is not to say that L2 Russian speakers rated Advanced (Low, Mid, or High) do not demonstrate control of aspect in OPIs. Advanced speakers' aspectual accuracy has been found to be high—89% to 92% percent accurate across the Advanced range, as one would expect by reading the ACTFL Guidelines (Robin, in press). But Robin found that that apparent accuracy owes itself to the high degree of lexicalization of frequently occurring verbs (40.5% in Advanced Low and Mid; 37.5% in Advanced High).…”
Section: Discussionmentioning
confidence: 82%